MENENTUKAN DETERMINAN SUATU MATRIKS DENGAN METODE CHIO - Saepudin, Asep (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2016)
Matrix theory is a branch of linear algebra that discussed in the mathematical sciences. Mathematical sciences play an important role in human life, it is necessary to solve problems that can not be solved directly. Thus, the problem can be transformed into the form of a mathematical model. One is the SPL (Linear Equation System). Various methods can be used to solve it. But for the SPL with a large variable can be solved by matrix methods, namely the inverse matrix. In the inverse matrix of the determinants involved. If the search value that ordo major determinant of the matrix (Ã°Ââ€˜â€º×Ã°Ââ€˜â€º), it would require an effective method. One is the method of Chio. Chio method can be applied to all square matrixas long as the element is Ã°Ââ€˜Å½11 not equal to zero (Ã°Ââ€˜Å½11≠0). Chio method of calculating the determinant of the matrix by decomposing determinant will look into sub-determinant of degree two (2×2) using the matrix element row 1 and column 1 as pointof departure. The decomposition is performed using the following sized matrix: Keywords: Matrix, Matrix Determinant, Chio method.